Papillary thyroid microcarcinoma with contralateral large humerus metastasis and cervical lymph node metastasis: A case report - Gong, Yi; Tang, Shixiong; Tan, Wanlin; Liao, Liyan; Li, Xiaodu; Niu, Chengcheng (Frontiers in Oncology, 2022)
Introduction: Papillary thyroid microcarcinoma (PTMC) rarely metastasizes to bone, especially metastasizes to contralateral humerus with so large mass is rare reported before. Case report: We presented a 50-year-old female patient with right large painful humerus mass for five years, presenting with swelling of the right shoulder with limited mobility. Positron emission tomography–computed tomography (PET/CT) showed a large mass in right humerus, bilateral lung lesions, and enlarged lymph nodes in right supraclavicular fossa. Right humerus lesion biopsy and immunohistochemical evaluations confirmed that the lesion originated from thyroid tissue. Then, the thyroid ultrasonography showed a hypo-echoic solid nodule with irregular taller-than-wide shape in the upper of left thyroid lobe, and enlarged lymph nodes with absence of fatty hilum in the contralateral right IV compartment. The total thyroidectomy and cervical lymph nodes dissection were undertaken, the histopathology confirmed the diagnosis of PTMC with contralateral cervical lymph nodes metastasis. Conclusion: We reported a case of PTMC with contralateral large humerus and cervical lymph nodes metastasis, and demonstrated the PET/CT images of the metastatic large humerus and thyroid ultrasonographic appearances of the PTMC and enlarged cervical lymph node.